History of technology - Inkster, Ian (London : Bloomsbury Academic, 2020)
"The technical problems confronting different societies in different periods and the measures taken to solve them form the concern of this annual collection of essays. Dealing with the history of technical discovery and change, the volumes in this series explore the relationship of technology to other aspects of life-social, cultural and economic-and show how technological development has shaped, and been shaped by, the society in which it has occurred."
Cover; Half-title; Title; Copyright; Contents; Editorial; The Contributors; Notes for Contributors; Special Issue: Patents in History; Introduction. An Imperfection of Institutions; Notes and References; Antecedents to Intellectual Property: the European Pre-history of the 'Ownership' of Knowledge; Antecedents To Intellectual Property; Greek Concepts About Owning Ideas; Roman Developments; The Middle Ages And The Rise Of Guild Knowledge; Some Early Patents; Some Early Copyrights; Conclusion; Notes and References. Inventions and Privileges in the Eighteenth Century: Norms and Practices. A Comparison between France and PiedmontIntroduction; The Uses Of Exclusivity In France: The Case Of John Kay; John Kay's First Privilege: A Juridical Hybrid; John Kay's Privilege Reshaped: A Flexible Right; An Inventor Under Contract: Innovation Outside Exclusivity; Conclusion; Notes and References; The Spanish Patent System (1770-1907); Introduction; The Institutional Environment; Evolution Of Registries And Basic Characteristics Of The System: Strong Technological Dependence. Applicants' Residence And Regional Distribution Of PatentsLegal Status And Socio-Professional Activity Of Applicants; Patents And Structure Of The Spanish Economy; Effectiveness And Duration Of Patents; Conclusion; Notes and References; The History of the First Patents for Steam Vessels in Russia; Prologue: The Idea Of Steam Vessels: Water-Moved And Horse-Moved Vessels; Robert Fulton; Charles Baird; Conclusions; Notes and References. European and Transatlantic Patent Transfer in the Salt Industry in the Era of Protoglobalization in the Last Quarter of the Nineteenth Century: Piccard's Salt Production PlantsIntroduction; A Global Patent In The Context Of Globalization And Protoglobalization; The Salt Industry In Europe And The Usa; Piccard's Salt Production Plants; Conclusion; Notes and References; Patents and Technological Change in Late Industrialization: Nineteenth-Century Mexico in Comparative Context; Introduction; Comparative Patent Law And The Case Of Mexico; Mexican Patenting In Comparative Perspective; Conclusion. Notes and ReferencesThe Management of Intellectual Property at Home and Abroad: Babcock & Wilcox, 1850-1910; Introduction; Patents And The Foundation Of The Firm; Patenting; Patenting Activity And The Company Board; The Technological Trajectory And Fields Of Babcock & Wilcox Patents; Patenting And Director/Employee Conflicts; Litigation; Threats Of Litigation; Patents And The Competence Of The Company; Conclusion; Notes and References; Patent Agents, Legal Advisers and Guglielmo Marconi's Breakthrough in Wireless Telegraphy; The Patent Agents; Marconi's Move To London; Carpmael & Co
Keywords: Technology; History; Science History